2018
DOI: 10.3892/br.2018.1114
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual frameworks of synthetic lethality in clear cell carcinoma of the ovary (Review)

Abstract: Abstract. Targeting non-oncogenes may result in the selective death of cancer cells. Clear cell carcinoma of the ovary (CCC) may exhibit resistance against conventional chemotherapy and is associated with poor prognosis. The aim of the present report was to review synthetic lethality-based therapies for CCC. Previous English-language studies were reviewed to accumulate preclinical and clinical data on targeting synthetic lethal partners. Synthetic lethal interactions have a variety of types, involving componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Many of them control cellular processes such as metabolism (including drug metabolism), DNA repair, differentiation, adhesion and apoptosis, and are involved in angiogenesis, progression or metastasis of cancer [31]. Recent studies on ovarian cancer revealed that BRG1 and BRM ATPases are mutually exclusive as their parallel inactivation leads to synthetic lethality [32], although other reports indicated the survival of cells with depletion of both ATPases [31]. One possible explanation of this apparent discrepancy may be the existence of shorter, truncated but functional versions of BRM protein which are simply not recognised by the anti-BRM antibody.…”
Section: Main Textmentioning
confidence: 99%
“…Many of them control cellular processes such as metabolism (including drug metabolism), DNA repair, differentiation, adhesion and apoptosis, and are involved in angiogenesis, progression or metastasis of cancer [31]. Recent studies on ovarian cancer revealed that BRG1 and BRM ATPases are mutually exclusive as their parallel inactivation leads to synthetic lethality [32], although other reports indicated the survival of cells with depletion of both ATPases [31]. One possible explanation of this apparent discrepancy may be the existence of shorter, truncated but functional versions of BRM protein which are simply not recognised by the anti-BRM antibody.…”
Section: Main Textmentioning
confidence: 99%
“…In this study, CDK1 was selected as a hub gene through bioinformatic analysis. To evaluate the potential of CDK1 as a prognostic biomarker for EOC, the expression of CDK1 was compared between EOC tissues and endometriosis lesions, which are considered to be precursors to EOC 20,21 . The relationship between CDK1 expression and clinicopathological features or prognosis data was assessed to determine the value of CDK1 in predicting the prognosis of EOC patients.…”
Section: Introductionmentioning
confidence: 99%